Pengaruh Kepemimpinan Visioner dan Kemampuan Komunikasi Kepala Sekolah Terhadap Kinerja Guru SD Negeri - Rosmiah Rosmiah; Bukman Lian; Muhammad Juliansyah Putra (CV. Ulil Albab Corp, 2026)
This study aims to analyze the influence of visionary leadership and principals’ communication skills on teachers’ performance at public elementary schools in Cluster I, Tanjung Lubuk District. The background of this research lies in the importance of principals’ roles in inspiring teachers and establishing effective communication to improve teaching quality. This research applied a quantitative approach with a survey method. The population consisted of all 60 teachers at public elementary schools in Cluster I, Tanjung Lubuk District, all of whom were taken as samples using the census technique. The data were collected through a closed-ended questionnaire based on a Likert scale that had been tested for validity and reliability. Data analysis was performed using multiple linear regression to determine both partial and simultaneous effects among the variables. The results revealed that principals’ visionary leadership had a positive and significant influence on teachers’ performance, as did their communication skills. Simultaneously, both variables contributed significantly to improving teachers’ performance. Therefore, effective visionary leadership combined with strong communication skills from the principal can enhance teachers’ professionalism and performance in public elementary schools in Cluster I, Tanjung Lubuk District.